Madrasah Head's Strategy for Improving the Quality of Teaching and Learning Islamic Religious Education - Hikmah, Badiatul; Imilyati, Dewi (Global Education Journal, 2025)
Islamic religious education has an important role in shaping students' character and noble morals. However, in its implementation, there are often various obstacles that impact the quality of learning. This research aims to find out the strategy of madrasah heads in improving the quality of the teaching and learning process of Islamic Religious Education at MA Darussalam Ngembe Beji. This study uses a qualitative approach with data collection methods through interviews, observations, and documentation. The study results show that madrasah heads apply several strategies, including academic supervision, evaluation of teaching and learning activities, coaching of teacher and student discipline, institutional promotion, infrastructure development, and contextual learning approaches. The supporting factors found included teacher involvement, relevant curriculum, adequate facilities, and community participation, while the inhibiting factors were time constraints, parental busyness, and the influence of the environment and mass media. The conclusion of this study is that the strategy implemented by the head of the madrasah can increase the effectiveness of Islamic Religious Education learning even though it still faces some external obstacles.